Criminal responsibility of military commanders (International Legal Practice) - Джурич, Олександр (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The problems relating to such a new institution of international criminal law as an institution of command responsibility considered. Analyzed the specific criminal cases considered by the international tribunals.